2017
DOI: 10.3892/mmr.2017.7279
|View full text |Cite
|
Sign up to set email alerts
|

XB130 enhances invasion and migration of human colorectal cancer cells by promoting epithelial-mesenchymal transition

Abstract: The expression of XB130 is associated with invasion and migration of many tumor cells, but its roles in human colorectal cancer (CRC) remains unknown. To investigate this, protein expression levels of XB130 in numerous human CRC cell lines were compared with a normal colorectal mucosa cell line by western blotting. Knockdown of XB130 using small interfering (si)RNA was performed to assess the effects on cell invasion and migration in a Transwell assay and a scratch test. Western blotting was also used to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These findings are consistent with previous studies on XB130 in a variety of cancers, e.g., thyroid tumor [19,31], prostate cancer [15], lung cancer [17], gastric cancer [32], breast cancer PLOS ONE [33], colorectal cancer [34], hepatocellular carcinoma [35], and skin tumor [24]. XB130 has been suggested to play significant roles in cancer progression through PI3K/Akt signaling pathway, leading to an increase in tumorigenic properties, including cell growth, migration, invasion and epithelial-mesenchymal transition (EMT) process [17,31,[35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies on XB130 in a variety of cancers, e.g., thyroid tumor [19,31], prostate cancer [15], lung cancer [17], gastric cancer [32], breast cancer PLOS ONE [33], colorectal cancer [34], hepatocellular carcinoma [35], and skin tumor [24]. XB130 has been suggested to play significant roles in cancer progression through PI3K/Akt signaling pathway, leading to an increase in tumorigenic properties, including cell growth, migration, invasion and epithelial-mesenchymal transition (EMT) process [17,31,[35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…To date, the function of XB130 protein has been well elucidated, but there has been limited research on the regulation of its expression (1)(2)(3)(4)(5)(6)10,19,(23)(24)(25)(26)(27). The present study indicated that the insertion of the 661-795 or 792-989 3'-UTR fragments into the psiCHECK-2 vector increased the luciferase activity of the reporter gene, compared with the Ctrl group.…”
Section: Discussionmentioning
confidence: 50%
“…FOXO3 inhibits AGS cell growth by promoting Beclin1-medicated autophagy and inhibiting p62 protein expression in an acidic microenvironment [55]. XB130 promotes human colorectal cancer cell migration and invasion by enhancing phosphorylation of FOXO3a and epithelial-mesenchymal transition [56]. DFOG, a novel synthetic genistein analogue, decreases the level of phosphorylated FOXO3a to inhibit the ovarian cancer sphere-forming cell self-renewal activity [57].…”
Section: Discussionmentioning
confidence: 99%